Developing the Tridatu Gastronomy Branding Blueprint for Tabanan Regency as a UNESCO Creative City - Wiguna, Kadek Surya Prasetya; Darma, Se Gede Sri (LifeSciFi, 2025)
This study develops a branding blueprint for Tabanan Regency to gain recognition as a UNESCO standard creative city in gastronomy. Tabanan has unique agrarian assets like the subak system, red rice from Jatiluwih, robusta coffee from Pupuan, and cocoa, but lacks a measurable strategy against UNESCO criteria. This study aims to assess Tabanan’s readiness to become a UNESCO Creative City of Gastronomy by identifying key gaps, structuring solutions through the City Model Canvas, and formulating strategic actions. Methods include documentation study, field observation, in-depth interviews, and focus group discussions with academics, business actors, communities, government, and media. A simple gap index converts qualitative data into scores, and strategies are built using the city model canvas. Findings show three commodities form the Tridatu Gastronomy brand, with high gaps in international collaboration, funding, and promotion, plus medium gaps in six other areas. The canvas produces a package with governance, festivals, certification, educational tours, campaigns, and a roadmap from 2025 to 2030. Tabanan can become Indonesia’s first gastronomy creative city by following this blueprint, preserving culture, raising income, and offering a model for similar regions.